سر سید احمد خان: ایک عہد ساز شخصیت: Sir Syed Ahmad Khan: As an Epoch-Making figure (Al-Qamar, 2023)
Sir Syed Ahmad Khan was a visionary who carved a space for rationalist thought, gave a new direction to education, and laid the parameters of modernist Urdu prose. He did not only evolve a new philosophy and pedagogy for public instruction and write remarkable discursive prose, but also affected a change in the attitude of people, especially of the Muslim community, towards social, cultural, and national identity. He was an iconoclast who promoted a scientific view of life and found space for pure rationalism as opposed to romantic sentimentality. As he also influenced poets and writers, he came to be acknowledged and valued as one of the major reformers of modern India.
Keywords: Sir Syed; Epoch-making; Figure